(untitled) (Journal of Asian Development Studies, 2025)
The study aims to throw light on the exploration of corpus-based semantic analysis of the titles of Pakistani drama. The objective of the research is to find out the semantic features of these titles. For this purpose, the study adopts the mix method approach in order to find out the frequency of these tags. For the study Conceptual Metaphor theory by Lakoff and Johnson (1980) was employed. For the analysis of the tags, USAS tagger tool was used to tag the titles. The data set consisted on 400 titles of four dominant channels of Pakistani media which were HUM TV, ARY, Har Pal Geo and Green Entertainment as per channel 100 dramas titles were collected from online sources. The analysis was done manually with the collection of the tags. The findings reveal that the highest used tag was Z5 that was dominant in all channels, with different frequencies as HUM TV got 89, ARY got 69, Har Pal geo got 49 and Green got 60. Thus the results show that the predominance of this tag indicates the important role of grammatical structures in the selection of the titles. Thus this study provides a pave path for the future researchers to explore other linguistic features in this domain of the titles of the dramas.